Examining the potential role of e-cigarettes to reduce health disparities associated with menthol cigarette use: Characterizing e-cigarette use, flavors, and reasons for use among US adults smoking menthol cigarettes. (1st July 2022) - Bold, Krysten W.; Buta, Eugenia; Simon, Patricia; Gueorguieva, Ralitza; Jackson, Asti; Suttiratana, Sakinah C.; Krishnan-Sarin, Suchitra; O'Malley, Stephanie S.
Abstract: Introduction: Menthol cigarette use contributes to disproportionate tobacco-related health disparities amongst minoritized race/ethnic groups. E-cigarettes are available in flavors such as menthol and may be a less harmful substitute among adults who smoke. Yet little is known about e-cigarette flavor preference and reasons for use by race/ethnicity among adults who smoke menthol cigarettes. Methods: Nationally representative PATH wave 4 adult data (Dec. 2016-Jan. 2018) were used to examine how menthol cigarette status and race/ethnicity were associated with past 30-day e-cigarette use, flavors used, and reasons for use with adjusted logistic regression models. Results: Menthol (vs. non-menthol) cigarette use was associated with higher odds of e-cigarette use (AOR=1.33, 95%CI=1.16–1.52). However, non-Hispanic (NH) Black and Hispanic individuals (vs. NH White) had lower odds of e-cigarette use (p's ≤ 0.004). In terms of flavor used, adults smoking menthol cigarettes and NH Black and Hispanic individuals had greater odds of using menthol/mint-flavored e-cigarettes (p's ≤ 0.02), and older adults (vs. 18–24-year-olds) had lower odds of using sweet-flavored e-cigarettes (p's < 0.0001). Regarding reasons for use, adults smoking menthol cigarettes had higher odds of reporting using e-cigarettes due to liking flavors (AOR=1.63, 95%CI=1.30–2.04), while NH Black adults had lower odds of liking flavors (AOR=0.64, 95%CI=0.43–0.96), and Hispanic adults had lower odds of using e-cigarettes to cut down on cigarette smoking (AOR=0.59, 95%CI=0.42–0.83). Conclusions: Findings suggest menthol flavored e-cigarettes may be important for adults who smoke menthol cigarettes, although racial disparities in current e-cigarette use and reasons for use may exacerbate tobacco-related health disparities. Highlights: Analyzed PATH survey data from adults who smoke to understand e-cigarette use. Menthol cigarette use was associated with higher odds of e-cigarette use. Black and Hispanic individuals had higher odds of using menthol e-cigarettes. Hispanic adults had lower odds of using e-cigarettes to stop smoking. Findings may help inform e-cigarette regulations.